Upaya Meningkatkan Motivasi Belajar Ipa Tentang Sumber Daya Alam Melalui Pendekatan Kontekstual Bagi Siswa Semester Ii Kelas IV Sdn Jembulwunut Gunungwungkal Pati Tahun Pelajaran 2014/2015 - Masruri, Masruri; , Drs. Muhammad Yahya, M.Si (2015)
The purpose of this research is to improve students' motivation to learn science through contextual approach. Researchers want to increase students' motivation to use contextual approach. Researchers planning the study using the principles of classroom action research. This study is divided into two cycles of the first cycle and the second cycle, each consisting of 2 meetings. Cycle I held on 24 and February 26, 2015 while the second cycle was carried out on 3 and March 5, 2015. The result is that after the first cycle executed an increase motivation to learn to be 55%. Once the researchers conducted the second cycle result is a significant increase in student numeracy competence has reached 95%. With the results, researchers feel the study was sufficient to meet the target of completeness that only 85%. The conclusions of this research is the use of a contextual approach can increase the motivation to learn science in the fourth grade SDN Jembulwunut Gunungwungkal Pati second semester of the school year 2014/2015.